Implementasi Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Untuk Meningkatkan Keaktifan Belajar IPA - luh made meriawati (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to improve the activeness of science learning in VB class 1 semester 2016/2017 students in Buruan 3 Public Elementary School by implementing theÂ  Cooperative type Two stay two stray (TSTS) learning model. This type of research was classroom action research (CAR) with 26 students of the first semester of 2016/2017 VB class research subjects. Learning activity data was collected by observation sheet. The data obtained were analyzed using descriptive statistical analysis. Based on the findings of the study and discussion, it could be concluded that the implementation of the Two Stay Two Stray type of cooperative learning model can increase the activeness of science learning in VB class 1 semester 2016/2017 students in Buruan 3 Public Elementary School. This result was proved from the average enhancement in the first cycle of 12.46 to 18.77 in the second cycle. The classical completeness of students also increased from 58.85% in the first cycle to 88% in the second cycle.